Interfacing pc (ISA-BUS) / Bakhari Mohd Nawi - Mohd Nawi, Bakhari (1999)
This project is developed for controlling On/Off two extemal 1-bit devices (ac powered fan and ac powered light bulb) using a personal computer. To achieve this, an input/output card was designed based on Intel 8255A, which is also known as I/O expander and controlled via a simple program which is being developed using Visual Basic (version 6). Out of the three ports available on 8255A, only port A bit 1 and bit 3 are being used. The input/output card is accessed via a software link library, Window 95IO.dll, which acts as a hardware (I/O card) and software (Visual Basic 6) interface.